Effectiveness of in insulin resistance correction and the adipokines level reduction in patients with arterial hypertension in comparison with other ARBs - S. V. Nedogoda; E. V. Chumachek; V. V. Tsoma; A. S. Salasyuk; V. O. Smirnova; E. A. Popova (Российский кардиологический журнал)
Aim. To assess the possibility of azilsartan medoxomil to achieve target blood pressure (BP) (less than 130/80 mm Hg), to study angioprotective features and reduction of adipokines levels and inflammatory markers in patients with hypertension and previous therapy with other ARBs.Material and methods. In open observational study with 24 weeks follow-up were included 60 patients with previous therapy (losartan or valsartan or telmisartan).All patients underwent ambulatory BP monitoring, applanation tonometry (determination of the augmentation index and central BP), measurement of the pulse wave velocity, laboratory tests (lipid profile, uric acid, fasting glucose, Homeostasis Model Assessment, homocysteine, leptin, adiponectin, highly sensitive C-reactive protein, tumor necrosis factor alpha, interleukin-6).Results. Azilsartan provided the systolic BP (29,05%, 22,5% and 8,9%) and diastolic BP reduction 18,82%, 20,46% and 8,54% (p<0,05) in patients previously treated with losartan, valsartan or telmisartan, respectively. Central systolic BP (by 25,95%, 8,78%, 11,94%), central pulse BP (by 40%, 18,38% and 19,6%), augmentation index (by 28,87%, 20,69% and 14,29%) and pulse wave velocity (by 21,57%, 24,56% and 24,92%) were decreased (p<0,05). There were positive changes in leptin, C-reactive protein, IL-6, adiponectin levels in all patients with losartan, valsartan or telmisartan initial therapy (p<0,05).Conclusion. Azilsartan medoxomil has advantages in BP control, the arterial elasticity improving, reducing of insulin-resistance and inflammation.